Application of electrical potential method to compact tension specimen - Gençer, Ferruh. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1981., 1981)
In this thesis "Electrical Potential Hethod" is considered. It is an experimental method to monitor sub-critical crack growth. Optimum locations for current and voltage leads and the calibration curve for compact tension specimen have been found using paper analogs. These results have been verified through metallic specimens. Sharp fatigue cracks are introduced in compact tension specimens and total crack lengths of these specimens have been estimated my means of the electrical potential technique. Real crack lengths are measured through a pocket comparator after heat tinting and separating the specimens into two. Results have been compared and discussed.
Keywords: Fracture mechanics.; Metals -- Fatigue.